Sociology through active learning : student exercises - McKinney, Kathleen (SAGE Publications, 2008)
"A great source for kinesthetic learning activities. I've used the book for designing my course for multiple learning styles."--Megan Thiele, University of California, IrvineThis student workbook is designed to allow you to easily integrate multiple active learning exercises into your Introduction to Sociology courses. Many teachers want to use "active learning" in their class, but don't have the materials commensurate with that pedagogy. These 51 active learning exercises have been carefully selected from a nationwide search of the best class-tested active le